Merging metallic catalysts and sonication: A periodic table overview - Domini, Claudia Elizabeth (2017)
This account summarizes and discusses recent examples in which the combination of ultrasonic waves and metal-based reagents, including metal nanoparticles, has proven to be a useful choice in synthetic planning. Not only does sonication often enhance the activity of the metal catalyst/reagent, but it also greatly enhances the synthetic transformation that can be conducted under milder conditions relative to conventional protocols. For the sake of clarity, we have adopted a structure according to the periodic-table elements or families, distinguishing between bulk metal reagents and nanoparticles, as well as the supported variations, thus illustrating the characteristics of the method under consideration in target synthesis. The coverage focuses essentially on the last decade, although the discussion also strikes a comparative balance between the more recent advancements and past literature.